Tomás Tamayo de Vargas y Augusta Emerita: corografía, hagiografía y la recuperación del pasado romano - García, Jorge Tomás (Rzym a Półwysep Iberyjski: Różnorodność relacji od starożytności po współczesność, 2019)
Of the many Antiquities that were used to illustrate the Utopia of the Golden Age in the seventeenth century, one of the most recurrent was that of Augusta Emerita. This process of literary recovery allows us to affirm that there were “emeritenses rebirths”. Tomás Tamayo de Vargas (1589–1641) bequeathed us one of the most valuable testimonies for the reconstruction of Augusta Emerita. Within the hagiographic fashion of his time, the Vitas Sanctorum Patrum Emeretensium was reissued. In his version, Tamayo de Vargas includes an appendix entitled Apospasmation. The purpose of the work is to gather testimony to document as accurately as possible its vision of the emeritense past. In this article, we present a critical study of the Latin work of Tamayo de Vargas, in addition to trying to define the cultural context in which the need to recover the Roman past of Mérida is generated. Este trabajo se encuadra en el contexto del “Grupo de Investigación de Excelencia Estudios Visuales” (Fundación Séneca, 19905/GERM/15)